The knowledge of impending heart attack and by-stander cardiopulmonary resuscitation among students at Turfloop University of Limpopo, South Africa - Nkoko, Koena Joseph (My University, 2007)
Aim of the study: To determine knowledge of CPR and heart attack or cardiac arrest signs and symptoms among university students. Study Design: A questionnaire based descriptive, cross – sectional study. Setting: University of Limpopo – Turfloop Campus in Limpopo Province of South Africa. Subjects: A total sample of 400 students participated in the study. The sample was selected randomly using simple random sampling techniques. Outcome measures: The faculty, age, gender and level of study were determined as well as the knowledge each student has on signs and symptoms of impending heart attack and CPR.Results: Of the 400 students only 26% (n=104) knew the signs and symptoms of an impending heart attack as well as out of hospital management of heart attack by performing CPR. There were differences between and within faculties, age groups, gender and level of study. Based on the Bonferroni test the student from faculty of Sciences, Health and Agriculture are more likely (p-value 0017) to know when to perform CPR compared to students from other faculties. Level of study is not associated (p-value 0128) with how much the students know about the timing and indications of CPR. Overall female students performed worse with 79% (n=123) responding incorrectly to the questions compared to 69% (n=169) males. Conclusion: Based on the results of this study it safely can be concluded that the students’ knowledge of signs and symptoms of an impending heart attack and CPR procedure is poor. It is therefore important for the university as a center of teaching and learning to consider including as part of university curriculum, basic life support and first aid courses which include CPR. The inclusion of basic life support and first aid in university curriculum will prepare students to be able to effectively manage out of hospital heart attack and reduce mortality resulting from the latter. The findings of this study might to a certain extent be reflecting what the public’s knowledge on the subject is, hence the need for the policy makers to take serious note of the findings when public health promotion programmes are developed.
Thesis (MPH) --University of Limpopo, 2007.
Keywords: Heart attack; Heart disease; Cardiopulmonary resuscitation; Myocardial infarction; Cardiac arrest; Cardiac resuscitation; Heart -- Disease